2018
DOI: 10.1093/jac/dky295
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of ceftazidime/avibactam as salvage therapy for treatment of infections due to OXA-48 carbapenemase-producing Enterobacteriaceae

Abstract: Ceftazidime/avibactam shows promising results, even in monotherapy, for the treatment of patients with severe infections due to OXA-48-producing Enterobacteriaceae and limited therapeutic options. The emergence of resistance to ceftazidime/avibactam was not observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(102 citation statements)
references
References 19 publications
6
89
1
6
Order By: Relevance
“…Although real-life experiences of ceftazidime-avibactam for the treatment of CRE is accumulating [9][10][11][12][13][14][15], data regarding its effectiveness and safety for the treatment of other gram-negative infections remain rare [16][17][18] and, to the best of our knowledge, are limited to only three single-center retrospective studies including a total of 20 patients. In the largest of these analyses, Santevecchi et al [17] reported a clinical success rate of 70% in ten multidrug resistant gram-negative infections treated with ceftazidime-avibactam.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although real-life experiences of ceftazidime-avibactam for the treatment of CRE is accumulating [9][10][11][12][13][14][15], data regarding its effectiveness and safety for the treatment of other gram-negative infections remain rare [16][17][18] and, to the best of our knowledge, are limited to only three single-center retrospective studies including a total of 20 patients. In the largest of these analyses, Santevecchi et al [17] reported a clinical success rate of 70% in ten multidrug resistant gram-negative infections treated with ceftazidime-avibactam.…”
Section: Discussionmentioning
confidence: 99%
“…Ceftazidime-avibactam is a new β-lactam/β-lactamase inhibitor currently approved by the European Medicines Agency for the treatment of complicated intra-abdominal infections [5,6], complicated urinary tract infections [7], hospital-acquired pneumonia (including ventilator-associated pneumonia), and more generally, for aerobic gram-negative infections with limited treatment options [8]. In real-life experiences, high rates of favorable response to ceftazidime-avibactam treatment are reported in patients with infections due to carbapenem−resistant Enterobacterales (CRE), with an overall success rate of about 70% [9][10][11][12][13][14][15], whereas post-marketing experience regarding the use of ceftazidime-avibactam for infections due to MDR-GNB other than CRE remains scarce [16][17][18] Moreover, information regarding features associated with clinical failures and the emergence of resistance in this group of patients are even scarcer. For this reason, in this multicenter study we describe our experience about the use of ceftazidime-avibactam for the treatment of infections due to MDR-GNB other than CRE in 13 Italian hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…15,21,22 The development of the new INCREMENT-SOT-CPE score was based on the INCREMENT-CPE score, which had been previously validated in the general population in different studies. 9,11,12,23,24 We used this strategy because there are no specific studies in SOT and many transplant groups use this predictive model, which takes into account variables important in any type of patient with BSI, including SOT. Besides, the inclusion of this general model in our new score reinforces the utility of the new model in posttransplant periods, such as the postoperative period, when the full impact of immunosuppression-derived from prolonged exposure to suppressive therapies-is still absent.…”
Section: Discussionmentioning
confidence: 99%
“…4 New -lactamase inhibitor combinations are beginning to provide alternatives, with trials or case series supporting superiority over colistin combinations. [5][6][7] Ceftazidime-avibactam is active against most Enterobacterales isolates with KPC and OXA-48-like enzymes, whilst meropenem-vaborbactam and imipenemrelebactam inhibit those with KPC enzymes only. 8,9 However, none of these combinations are active against Enterobacterales with MBLs, nor against the vast majority of carbapenemase-producing Pseudomonas aeruginosa and Acinetobacter baumannii.…”
Section: Introductionmentioning
confidence: 99%